Application Development on Cloud Environment - Gill, Simarpreet kaur (My University, 2010)
Cloud computing has become a buzzword of today. Cloud computing is not a completely new concept; it has intricate connection to the established Grid Computing paradigm, and other relevant technologies such as utility computing, cluster computing, and distributed systems in general. In this thesis, we have demonstrated the use of cloud by developing an application on cloud environment (Google App Engine).
M.E. (Software Engineering)
Keywords: Cloud Computing; Google App Engine